Characterization of Tannery Effluent and Efficiency Assessment of Central Effluent Treatment Plant (CETP) at Savar in Bangladesh - Monira, U.; Sattar, G. S.; Golam Mostafa, Md. (Asian Journal of Science and Applied Technology, 2023)
The industry discharges a large volume of effluent, many of which contain lots of chemicals and toxic substances that have the potential to cause distress to the environment. The study focused on analyzing various physicochemical parameters of the effluent discharge from the Central Effluent Treatment Plant (CETP) at the Savar Tannery Industrial Zone. The effluent was collected four times (pre-monsoon, monsoon, and post-monsoon) a year, from 2021-2022. The effluent was inspected for vital water quality parameters, such as pH, COD, BOD, TDS, TSS, NO3-, SO42-, HCO3-, PO43-, Cl-, Na, Ca, Cr, Fe, Cu, Zn, and Pb. Most of the parameters exceed the standard permissible limit of the Department of Environment, Bangladesh (DoE, BD), NQES, and ISW-BDS for inland water. The mean concentrations of COD, BOD, TSS, and Cr were 337, 97.5, 209, and 6.1 mg/L, and these values were far above the permissible limit with a removal efficiency of 51%. The study observed that industrial discharge of unproperly treated effluent deteriorates the surface water quality and causes huge threats to aquatic life and sustainable water resource management.